Proteolysis in the quiescent seed - Duarte, I. C.; Ricardo, C. P. P.; Duque-Magalhães, M. C. (Physiologia Plantarum, 1996)
The importance of the proteolytic system of the quiescent seed in regard to mobilization of storage protein was assessed by identification of proteases already present at this stage. Extracts of quiescent cotyledons of white lupin (Lupinus albus) submitted to 45 h autolysis in vitro displayed a higher degree of protein degradation than that observed in vivo after two days of seed imbibition. Differences in the susceptibility to proteolysis were verified by densitometric analysis of the polypeptides after electrophoretic separation. The pH dependence of the proteolytic activities and the responses to specific protease inhibitors showed that the proteolytic systems vary from quiescent to 1 - to 3-day-imbibed cotyledons. By labelling an endogenous globulin with 125I a sensitive radiometric assay allowed the identification of both an acidic and a neutral proteolytic system in the quiescent cotyledon. Within the quiescent seed there already exists a high potential for initiating proteolysis, so that the requirement for proteolysis by specific endopeptidases synthesized de novo upon imbibition only applies to part of the reserve proteins.